Principles Of Human Relation With Professional Organizations In The Light Of Islamic Law: Theoretical And Diagnostic Study - Taghri, Imane; Larite, Bachir (Journal of Human Sciences, 2023)
This study aims to know the most important principles of human relations with professional organizations in the light of Islamic law (the book and the Sunnah). The study concluded that Islamic thought attaches great importance to the human dimension, since human relations in business organizations play an important and predominant role in the social life of the individual in general, and his professional life in particular.